Entrepreneurship Assistance and Basic Financial Bookkeeping for Small to Medium Industries UD. Omah Nurjanah - Ayu Agus Tya Ningsih; Ratnawati; Yayuk Ngesti Rahayu; M. Taufiq Noor Rokhman; Eko Yuniarto (Asian Journal of Community Services, 2023)
This community service program aims to educate business actors in UD IKM. Omah Nurhanah Malang which operates in the cracker processed food industry. The main problems often faced by business actors include the lack of awareness of keeping business financial records due to a lack of knowledge about financial bookkeeping, resulting in a business financial system that cannot differentiate between business profits and personal cash and decreased motivation when faced with business problems, resulting in has an impact on the low level of carrying out new innovations. The method used is entrepreneurial motivation training and simple financial bookkeeping. The result of this service is that business actors understand how to do good entrepreneurship through financial recording, as well as increasing business motivation.